Teaching Organic Chemistry in Higher Education Institutions - Genzhemuratova Gulkhan Perdebayevna (Zien Journals, 2022)
The performance of synopsis and individual homework on topics (sections) allocated to the student's independent work is checked by the teacher in each practical lesson and recorded in the group Journal.
Keywords: Student independently chooses one of the method; independently chooses one of the methods propose